2022
DOI: 10.3389/fonc.2022.887157
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Size With Prognosis in Patients With Resectable Endometrial Cancer: A SEER Database Analysis

Abstract: This study aimed to explore the relationship between tumor size (Ts) and prognosis in endometrial cancer (EC). A total of 52,208 patients with EC who underwent total hysterectomy were selected from the Surveillance, Epidemiology, and End Results Program database. Overall survival (OS) and endometrial cancer-specific survival (ESS) were chosen as survival outcomes. The Cox proportional hazards model was used to explore the effect of Ts on prognosis. The restricted cubic splines based on the Cox regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…We found that the maximum tumor diameter significantly differed between risk groups, echoing previous findings that larger tumor sizes are associated with poorer prognoses [35,36]. The invasive features prevalent in the non-low-risk groups align with the findings of other studies, such as those of Maria Ali et al and Stephanie Nougaret et al, which linked tumor size to lymph node metastasis and myometrial invasion depth, respectively [37,38].…”
Section: Discussionsupporting
confidence: 89%
“…We found that the maximum tumor diameter significantly differed between risk groups, echoing previous findings that larger tumor sizes are associated with poorer prognoses [35,36]. The invasive features prevalent in the non-low-risk groups align with the findings of other studies, such as those of Maria Ali et al and Stephanie Nougaret et al, which linked tumor size to lymph node metastasis and myometrial invasion depth, respectively [37,38].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we found that tumor size was an important prognostic factor. Xuefei Hou et al 32 also found a nonlinear relationship between tumor size and prognosis in patients with endometrial cancer, and the risk of death elevated monotonically with the increase in tumor size.…”
Section: Discussionmentioning
confidence: 94%
“…Phạm Văn Bùng nghiên cứu năm 2004 ghi nhận tỉ lệ giai đoạn I chiếm tỉ lệ 56,2% [3]. Dữ liệu trong nghiên cứu SEER ghi nhận tỉ lệ này là 69,2% [5]. Các tỉ lệ này thấp hơn trong nghiên cứu của chúng tôi vì báo cáo trên dân số chung, trải dài trên tất cả các giai đoạn của bệnh.…”
Section: đặC đIểm Lâm Sàng Cận Lâm Sàng Của đốI Tượng Nghiên Cứuunclassified